Analisis Spasial Kerentanan Erupsi Gunung Marapi Terhadap Wilayah Permukiman - Erfis Aisyiah Dwi Citra Utami; Hermon, Dedi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
This research aims to analyze the spatial vulnerability of Mount Marapi eruption to residential areas. The type of research in this study is quantitative. This research is a geographic research using an ecological/environmental approach. This research was conducted in Agam Regency and Tanah Datar Regency, precisely the sub-districts on the slopes of Mount Marapi with a radius of 7 km. Based on the results of data processing on the total vulnerability of the Mount Marapi eruption area, there are 4 nagari that have a high level of vulnerability to the eruption of Mount Marapi. The areas found in this high vulnerability are dominated by the number of settlements and the high number of residents, both vulnerable age population and poor population. Recommendations for handling the high vulnerability of the eruption of Mount Marapi are limiting the construction of houses in vulnerable areas of Mount Marapi, rearranging settlement space in nagari with high population density, suppressing population growth in vulnerable areas of Mount Marapi eruption, protecting and managing natural forest areas, protected forests and shrubs, limiting and supervising the expansion of productive land.